Development of Interactive E-Module on The Periodic System Materials as an Online Learning Media - Syahrul Wahyu Rahmatsyah; Kusumawati Dwiningsih (Postgraduate, University of Mataram, 2021)
The purpose of this research is to determine the feasibility, effectiveness, and practicality of learning media in the form of an interactive e-module with the research method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate) which is modified into 3D. The instruments used consisted of review sheets, validation, student response questionnaires, tests (pretest and posttest). The data were obtained based on the results of interviews with chemistry teachers and giving questionnaires to students. The results of the validation of this device got the score of 90% for content criteria, 93% for presentation criteria, 84% for language criteria, and 100% for graphic criteria are very feasible to use. The practicality of the e-module is known from the results of the responses of students with an average score of more than 81% which can be categorized as highly responding. The interactive e-module is also said to be very effective by analyzing learning outcomes using the t-test with a significance value of 5%. Therefore, the use of interactive e-modules on the element periodic system material can be used as learning media in carrying out online learning activities